A Survey on Privacy Protected Facial Biometric Verification (International Journal of Engineering and Computer Science, 2016)
Today the use of security cameras or the surveillance cameras has been increased dramatically. Why because the cameras and networks become cheaper and also these cameras provide a feasible amount of security to the society. But the important thing is that the system should achieve two goals: it should perform face recognition for the security purpose and also the system should provide privacy protection for the individuals who are captured in those cameras. In simple words their face image should not browse without permission or it cannot be misused for any other purpose. Many solutions have been proposed to achieve these two in a surveillance system. The first solution was cryptographic encryption and later face scrambling has been proposed.  In this paper we discuss about different techniques used for the privacy protection as well as face recognition and also a comparison between these methods are performed to evaluate these techniques.